Methane Aromatization in a Fluidized Bed Reactor: Parametric Study - Lasobras, Javier; Soler, Jaime; Herguido, Javier; Menéndez, Miguel; Jimenez, Alonso; da Silva, Mariana; Franco, María J.; Barrio, Izaskun; Làzaro, Jesús (Frontiers in Energy Research, 2019)
Methane aromatization is a promising technology for the transformation of natural gas to liquid products, but suffers the problem of catalyst deactivation by coke. A Two-zone fluidized bed reactor has been proposed as a tool to counteract the catalyst deactivation, by providing continuous catalyst regeneration in the same vessel where the main reaction is carried out. This work shows the effect of the main operating conditions (carburization temperature, reaction temperature, carburization time, nature of regenerating agent and feed flow and height of the hydrocarbon entry point) .